Preservation strategy through implementation of Hindu aesthetics on Balinese Pejaten pottery in Indonesia - Priscilla Tamara; Gabriel Roosmargo Lono Lastoro Simatupang; Gustami Gustami; I Wayan Senen (International Journal of Visual and Performing Arts, 2021)
Pejaten pottery is one of the aesthetically unique potteries. The pottery has various ornaments such as god ornaments, god weapons, barong, and animals and plants. These ornaments are often found in Hindu worship ceremonies. This shows that, aesthetically, Pejaten pottery cannot be separated from Hindu aesthetics, so it is interesting to study. The problem is how the implementation of Hindu aesthetics in Pejaten pottery works and how Hindu aesthetics is used as a strategy for preserving Hindu aesthetics in Pejaten pottery. This study aims to determine the basis for applying Hindu aesthetics as a strategy for preserving Pejaten pottery. This qualitative research took the location of Pejaten Village, Kediri District, Tabanan Regency, Bali. Data were collected by direct observation, interviews, and also collecting literature data related to Hindu aesthetics. The aesthetic analysis process of Pejaten pottery is carried out using the concepts of Rwa bhineda (balance), satyam (truth), sivam (holiness), sundaram (beauty), and Pangider Bhuana (Pangider-ider). This study indicates that the ornaments and various forms of Pejaten pottery have a strong Hindu philosophical foundation, and this shows the religious nature of the Pejaten pottery craftsman. The conclusion is that the religiosity of the Pejaten pottery craftsmen is very influential in their creative process, and this is significantly able to maintain the preservation of the Hindu aesthetics of Pejaten pottery, Bali